2017
DOI: 10.1039/c7ta03108d
|View full text |Cite
|
Sign up to set email alerts
|

Future high-energy density anode materials from an automotive application perspective

Abstract: Several future anode active materials are critically evaluated against the energy, power and lifetime targets for high-energy density automotive applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 144 publications
1
110
0
2
Order By: Relevance
“…An adequate fit of the P 2p signal required two binding states to be considered. In accordance with Zhang et al, the main signal at 132.0 eV (P 2p 3/2 ) marked by the green area in Figure 5b was assigned to phosphorus in a tetrahedral coordination with sulfur, namely to the PS 4 3− units in LSPS. 43 A second signal at 132.9 eV (marked in blue) might originate from P-[S] n -P type bonding configurations, e.g.…”
Section: Identification Of the Decomposition Products-in Order To Idsupporting
confidence: 88%
See 1 more Smart Citation
“…An adequate fit of the P 2p signal required two binding states to be considered. In accordance with Zhang et al, the main signal at 132.0 eV (P 2p 3/2 ) marked by the green area in Figure 5b was assigned to phosphorus in a tetrahedral coordination with sulfur, namely to the PS 4 3− units in LSPS. 43 A second signal at 132.9 eV (marked in blue) might originate from P-[S] n -P type bonding configurations, e.g.…”
Section: Identification Of the Decomposition Products-in Order To Idsupporting
confidence: 88%
“…15 LiTFSI | SS cells where the lithium electrodes were replaced by stainless steel blocking electrodes showed an analogous impedance increase which could be ascribed to a growing impedance at the LSPS | PEO 15 LiTFSI interface caused by a reaction between these two materials. Subsequent XPS analysis, 31 P MAS NMR, and UV-Vis spectroscopic tests of the aged LSPS | PEO 15 LiTFSI interface revealed polysulfides, P-[S] n -P type bridged PS 4 3− units and sulfite as decomposition products. Additional experiments showed that artifacts due to reaction of LSPS with trace water impurities as well as the reaction of LSPS with the conductive salt LiTFSI could be ruled out as possible causes for the observed LSPS degradation.…”
Section: Discussionmentioning
confidence: 99%
“…As arenewable energy source,hydrogen (H 2 )holds great promise in replacing traditional fossil fuels,w hich has yet to be fully realized. [54] Electrocatalytic water splitting is one of the most cost-efficient and cleanest methods to produce H 2 that is very pure compared with that produced chemically.In ab road sense,t his consists of two half reactions:c athodic hydrogen evolution reaction (HER) and anodic oxygen evolution reaction (OER). [55] Compared with HER, OER is kinetically unfavorable, [56] consequently,O ER has been regarded as the rate-limiting step in water splitting.…”
Section: Electrochemical Energy Conversionmentioning
confidence: 99%
“…[54] Die elektrokatalytische Wasserspaltung ist eine kostengünstige und saubere Methode zur Herstellung von H 2 ,d as gegenüber chemisch synthetisiertem H 2 sehr rein ist. [54] Die elektrokatalytische Wasserspaltung ist eine kostengünstige und saubere Methode zur Herstellung von H 2 ,d as gegenüber chemisch synthetisiertem H 2 sehr rein ist.…”
Section: Elektrochemische Energieumwandlungunclassified
“…Als erneuerbare Energiequelle hat Wasserstoff (H 2 )e ine große Bedeutung fürd en Ersatz herkçmmlicher fossiler Energieträger. [54] Die elektrokatalytische Wasserspaltung ist eine kostengünstige und saubere Methode zur Herstellung von H 2 ,d as gegenüber chemisch synthetisiertem H 2 sehr rein ist. Es laufen zwei Halbreaktionen ab:d ie kathodische Wasserstoffentwicklungsreaktion (HER) und die anodische Sauerstoffentwicklungsreaktion (OER).…”
Section: Elektrochemische Energieumwandlungunclassified